PENGELOLAAN AIRTANAH YANG BERWAWASAN LINGKUNGAN OLEH INDUSTRI AIR MINUM DALAM KEMASAN (AMDK) - -, T. Yan W. M. Iskandarsyah; -, Hendarmawan (Fakultas Teknik Geologi Universitas Padjadjaran, 2010)
Sustainability of production of bottled drinking water is highly dependent and influenced by the condition of the recharge zone. Thus, knowledge and understanding of local conditions and the behavior of groundwater recharge to the springs is required. To get a decent source of water produced and minimize the impact can inflict negative, then P.T. Tirta Investama implemented several stages such as literature study, identifying the area, a preliminary survey, detail survey, EIA studies, the production (construction and installation), and recharge area study at least one year. Protection of water resources taken from the aquifer is not used by people around in general (aquifers) as well as against the source of water which is generally utilized by the population (unconfined aquifer) translated in the construction of a well borehole. Meanwhile, study catchment areas become the crucial factor in the management of groundwater, natural feedback input is one of the factors associated with the process of infiltration.From this study obtained distribution of the origin of groundwater (recharge) to the water that comes out (discharge) and the layers that tend vulnerable to groundwater contamination. Studies recharge area for a minimum of one year is a very important study as sustainable groundwater resource management efforts in order water balance in a region.